Resilience in Children Undergoing Stem Cell Transplantation: Results of a Complementary Intervention Trial - Phipps, Sean (American Academy of Pediatrics, 2012)
BACKGROUND: Children undergoing stem cell transplantation (SCT) are thought to be at risk for increased distress, adjustment difficulties, and impaired health-related quality of life (HRQL). We report results of a multisite trial designed to improve psychological adjustment and HRQL in children undergoing SCT. METHODS: A total of 171 patients and parents from 4 sites were randomized to receive a child-targeted intervention; a child and parent intervention; or standard care. The child intervention included massage and humor therapy; the parent intervention included massage and relaxation/imagery. Outcomes included symptoms of depression and posttraumatic stress, HRQL, and benefit finding. Assessments were conducted by patient and parent report at admission and SCT week+24. RESULTS: Across the sample, significant improvements were seen on all outcomes from admission to week+24. Surprisingly, patients who had SCT reported low levels of adjustment difficulties at admission, and improved to normative or better than average levels of adjustment and HRQL at week+24. Benefit finding was high at admission and increased at week+24; however, there were no statistically significant differences between intervention arms for any of the measures. CONCLUSIONS: Although the results do not support the benefits of these complementary interventions in pediatric SCT, this may be explained by the remarkably positive overall adjustment seen in this sample. Improvements in supportive care, and a tendency for patients to find benefit in the SCT experience, serve to promote positive outcomes in children undergoing this procedure, who appear particularly resilient to the challenge.